1, 3-Difunctionalization of alkenes: state-of-the-art and future challenges. Issue 24 (18th October 2021) - Wang, Dong-Kai; Li, Long; Xu, Qing; Zhang, Jianfeng; Zheng, Hongxing; Wei, Wen-Ting
Abstract : This review summarizes the advances in 1, 3-difunctionalization of alkenes mediated by Pd-, Ni-, Fe-, and Cu-based catalysts, as well as under metal-free conditions, with an emphasis on the reaction mechanisms and factors governing regioselectivity. Abstract : The direct difunctionalization of alkenes has emerged as a sustainable and versatile strategy for the efficient construction of complex molecules from simple chemical feedstocks. Specifically, the 1, 3-difunctionalization of alkenes enables the simultaneous installation of functional groups at the non-classical 1, 3-position of alkenes. Thus, these chemical transformations create new bond disconnection strategies in chemical synthesis. This emerging strategy has identified a novel pathway for the further development of alkene transformations, and has even been applied to the synthesis of various complex biologically active molecules and pharmaceutical candidates. This review summarizes the advances in the development of 1, 3-difunctionalization of alkenes mediated by Pd-, Ni-, Fe-, and Cu-based catalysts, as well as under metal-free conditions, over the past few decades, with an emphasis on the reaction mechanisms and factors governing regioselectivity.